INTERESTS OF STUDENTS IN ORIENTAL WRESTLING AND BOXING - Abdurasulov, Rustam (Журнал Педагогики и психологии в современном образовании, 2024)
This article shows the socio-psychological characteristics of students ’ interest in Oriental Solo Wrestling and boxing.